2020
DOI: 10.1088/1755-1315/572/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose, sucrose, and lactose solution on the stability of betacyanin pigment from red dragon fruit (Hylocereus polyrhizus) peels

Abstract: People use peels, stems, leaves, and fruits of plants as a natural colorant. One part of fruit peel that has potentially used as a food colorant is red dragon fruit peels. The pigments found are betacyanin, but betacyanin compounds are easily degraded by heat, pH, and light. Degradation of betacyanin forms betalamic acid compounds (yellow) and cyclo-DOPA acids (cloroless). In this work, an attempt was made to increase the stability of betacyanin pigment against temperature by adding stabilizer such as glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…When exposed with the hot air drying, the degradation of betacyanin pigment has occurred. It was reported by Pamungkas et al (2020) that upon heating, betacyanin was found to decompose into yellow degradation products, which led to decrease in red values (a*) while increase in the yellow (b*) colour. However, increasing the concentration of foaming agents of EA with decrease the ratio or RFP puree has caused increase in b* values for blueness.…”
Section: Table 5 Colour Properties Of Foam-mat Dried Rfp Powdermentioning
confidence: 99%
“…When exposed with the hot air drying, the degradation of betacyanin pigment has occurred. It was reported by Pamungkas et al (2020) that upon heating, betacyanin was found to decompose into yellow degradation products, which led to decrease in red values (a*) while increase in the yellow (b*) colour. However, increasing the concentration of foaming agents of EA with decrease the ratio or RFP puree has caused increase in b* values for blueness.…”
Section: Table 5 Colour Properties Of Foam-mat Dried Rfp Powdermentioning
confidence: 99%
“…However, T1 treatment indicated the maximum sensory scores in taste, consistency, smell, and overall acceptability; while T3 treatment received the highest hedonic score for color attribute. RD fruit's peel contains betacyanin pigment, which contributes to the reddish coloration in yogurt and is thus favored by most of the panelists (Pamungkas et al, 2020). Similarly, addition of RD peel powder to a certain extent seemed to improve consumer expectations regarding taste and smell, since several volatile and nonvolatile bacterial metabolites, as well as carbonyl chemicals, contribute to the flavor of yogurt (Cheng, 2010).…”
Section: Sensory Attributes Of Fortified Yogurtsmentioning
confidence: 99%